2021
DOI: 10.1002/agj2.20787
|View full text |Cite
|
Sign up to set email alerts
|

Base cation saturation ratios vs. sufficiency level of nutrients: A false dichotomy in practice

Abstract: Base cation saturation ratio (BCSR) or "soil balancing" is a soil management philosophy which strives to maintain targeted base cation saturation percentages in soil.Despite lack of Land Grant University (LGU) endorsement for decades, BCSR is widely practiced by many farmers in the United States, particularly in the organic farming community. Here, we explore BCSR persistence and present a framework around BCSR that reflects how it is conceived and practiced on working farms, with a key premise that BCSR pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Future research on the use of conservation tillage in the context of organic farming could provide important insights for adapting current systems and improving the environmental footprint of organic corn production [47][48][49]. Likewise, producers use a wide range of purchased products on their organic corn fields, many of which have received little attention from the scientific community [50] and should be further explored in terms of their agronomic and economic benefits for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Future research on the use of conservation tillage in the context of organic farming could provide important insights for adapting current systems and improving the environmental footprint of organic corn production [47][48][49]. Likewise, producers use a wide range of purchased products on their organic corn fields, many of which have received little attention from the scientific community [50] and should be further explored in terms of their agronomic and economic benefits for farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Given the lack of positive effects of BCSR management on crop yields in published studies (Kopittke & Menzies, 2007;Chaganti et al, 2021), we questioned whether the positive benefits attributed to a higher Ca:Mg ratio by BCSR practitioners could be due to increasing soil pH, rather than increasing Ca saturation levels, both of which typically occur after lime application (Culman et al, 2021). Thus, we hypothesized that optimizing soil pH, not Ca:Mg ratio, would increase grain yields, and that optimizing Ca:Mg ratio without managing soil acidity would have little effect on yields.…”
Section: Core Ideasmentioning
confidence: 99%
“…Calcium and Mg are essential nutrients for plant growth (Hirschi, 2004; Shaul, 2002), but their role in soil, particularly their relative influence on soil structure, is not well understood (Chaganti & Culman, 2017; Culman et al., 2021). Calcium plays a role in improving soil aggregation by complexing to organic matter substrates and to the negatively charged surfaces of clay particles (Clough & Skjemstad, 2000; Rowley et al., 2018; Six et al., 2004), playing a putatively important role in soil organic carbon stabilization (Rowley et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent reports also recorded perceived positive impacts and long-term use of BCSR among many American farmers (Brock et al 2020;Culman et al 2021) as well as its continuing efficacy studies (Souza et al 2016;Bonomelli et al 2019;Chaganti et al 2021). Some researchers and soil scientists designated that the BCSR approach is also essential in terms of lime, gypsum, soil acidity, and cation competition study (Webster 1985;van Biljon et al 2007;Wood & Litterick, 2017;Culman et al 2021). Biswas et al (2019) suggested that (Ca + Mg)/K ratiogoverned the grain yield of rice.…”
Section: Soil Fertility Statusmentioning
confidence: 99%
“…This concept theorized that the decrease of crops yield response occurs while the soil nutrients concentration is approaching sufficient level (McLean, 1977). Several researchers have reported the BSCR and SLAN study in subtropical soil (Eckert & McLean, 1981;Liebhardt, 1981;Favaretto et al 2008;Brock et al 2020;Culman et al 2021). However, the research conducted in tropical soils, especially in the study area were found scarce (Hikmatullah & Al-Jabri, 2007;Anda, 2012;Assefa et al 2020;Kasno et al 2021).…”
Section: Introductionmentioning
confidence: 98%